A Comprehensive Review of the Literature on IT Governance and Company Performance - KAFANDO Benoit; THIOMBIANO Noël; PELENGUEI Essohanam; BAZIE Porto (Journal of Management Research, 2024)
Purpose – This study provides a comprehensive review on the analysis of the current trend of IT governance publications and literature on IT governance and company performance. Methodology – The method of document analysis is used to collect the data published from 1992 to 2022 in the fields such as business and management studies, finance and accounting, corporate governance, and information technology. Scope of the study – This study revolves around the analysis of the current trend of IT governance publications and a literature on IT governance, including corporate governance and its relationship with corporate governance of IT, its meaning, mechanisms, IT governance standards from international and Malaysian best practices, and the effect of IT governance on company performance. Findings – Previous studies have found that adopting IT governance helps companies to achieve higher profits. However, the findings of the analysis revealed that there is still little research on the effect of IT governance on company performance. Although board and management involvement are important to ensure a high return on IT investment, the effect of these two elements on company performance has not been examined in previous studies. Practical Implications – The findings provide researchers with knowledge on IT governance that can improve the way companies conduct their IT and enhance their performance. Originality/ Value – This study is unique in that as it focuses on a comprehensive review of the analysis of the current trend of IT governance publications and a literature review on IT governance. The findings provide a clear picture of how the future research can be conducted by incorporating the effects of IT governance mechanisms, boards and management involvement on company performance.